Expert evaluation of a web-based grammatical competence module: Fuzzy Delphi method - Nur Hidayah Md Yazid; Nur Ainil Sulaiman; Harwati Hashim (Institute of Advanced Engineering and Science, 2026)
Web-based learning modules have been considered indispensable for English as a second language (ESL) learners to utilize autonomously. However, there are still not many reputable grammatical competence modules designed for the transition between secondary school and undergraduate levels. Thus, this study aimed to ascertain expert consensus on developing a web-based grammatical competence module for pre-university ESL learners. The Fuzzy Delphi method (FDM) was employed in this study to create the module. Four broad constructs, which are the design, technical aspects, content, pedagogy of the website were used as references in developing a survey as the instrument for the study. The features in the survey were evaluated by six selected experts based on established criteria for high-quality language learning websites. Data analysis was undertaken using a 5-point fuzzy scale and the Fuzzy Delphi approach Logic Software (FUDELO 1.0). Supported by the findings and a consensus rate of over 75%, a cut-off value (d) of ≤0.2, and a fuzzy score (A) of ≥α-cut value=0.5, expert consensus was reached for the four constructs. The findings support that the module is fitting for pre-university ESL learners and can be used as a supplementary grammar learning module. Empirical studies related to learner performance and engagement outcomes in the future must continue assessing the long-term effectiveness of the module and ensure its long-term efficacy in ESL learning.